CHF Strength and Swiss Export Performance – Evidence and Outlook From a Disaggregate Analysis - Raphael Auer; Philip Sauré (Swiss National Bank, Study Center Gerzensee, 2011)
Why has Swiss export performance been so strong during the past quarters despite the marked appreciation of the CHF? What is the outlook for Swiss exports given the still elevated CHF? In this paper, we shed light on these questions by analyzing a panel of Swiss exports disaggregated along both the regional and the industry dimension. To explain the export performance of the recent past, we estimate how the exchange rate and demand growth in each export market affect trade flows and also, how this varies across different industries. The appreciation of the CHF has considerably dampened Swiss export performance. As a counterfactual, we ask how Swiss exports would have developed had the CHF stayed flat against other currencies during the 5 years leading up to October 2010. Compared to this scenario, the Swiss export industry has already lost a cumulative of CHF 35 billion in revenues due to the CHF appreciation. At the current juncture, monthly exports are reduced by CHF 2.7 billion (around 17%). We show that the key reason for the strong export performance despite the CHF strength was the rebound in global demand in the aftermath of the financial crisis. Moreover, we also document that the timing of global demand growth has completely masked the effect of the CHF strength: during the last quarters, periods of pronounced CHF appreciation always coincided with strong recovery of global demand. Failure to account for this coincidence could lead to the wrong assumption that the exchange rate matters very little for Swiss export performance. Last, to gauge the likely evolution of Swiss exports and their regional composition in the years to come, we combine our estimation results with the regional GDP and exchange rate forecasts provided by the Swiss National Bank. Following this approach, we predict that over the next three years, Swiss exports will rise a combined 16%, with little less than half of this increase going to Emerging Asia and 30% to the euro zone. We also document the key industries that will drive Swiss export growth in the near future.
Keywords: 330; Schweizer Franken; Aufwertung; Export; Handelseffekt; Schweiz